1981
DOI: 10.1088/0029-5515/21/3/006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of end-cell stability on the confinement of the central-cell plasma in TMX

Abstract: In the Tandem Mirror Experiment (TMX), the central-cell losses provide the warm unconfined plasma necessary to stabilize the drift-cyclotron loss-cone instability in the end cells. This places a theoretical limit on central-cell confinement, which is expressed as a limit on the end-cell to central-cell density ratio. As this density ratio increases in a TMX experiment, large increases of end-cell ion-cyclotron-frequency plasma fluctuations are observed. These fluctuations cause the central-cell confinement to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…The observed correlation between RF activity (V pp , sensed by electrostatic probes external to the central plasma) and the efficacy of plugging, as reflected by m c , is shown in Fig. 87, taken from the report of Drake et al [339]. It was found that the loss of confinement time due to RF activity could be modelled by an expression of the form [340] TABLE XIX.…”
Section: Fig 87 Tmx Data On Loss Of Plugging Caused By the Onset Of R...mentioning
confidence: 93%
“…The observed correlation between RF activity (V pp , sensed by electrostatic probes external to the central plasma) and the efficacy of plugging, as reflected by m c , is shown in Fig. 87, taken from the report of Drake et al [339]. It was found that the loss of confinement time due to RF activity could be modelled by an expression of the form [340] TABLE XIX.…”
Section: Fig 87 Tmx Data On Loss Of Plugging Caused By the Onset Of R...mentioning
confidence: 93%
“…This was eventually supported by Doppler broadening measurements which indicated that central cell ion temperatures might be as high as 100-200 eV [10]. Theory now indicates that radio-frequency (RF) fluctuations generated in the end cells couple to the central cell ions and heat them [11]. Increased RF fluctuations were also associated with decreased ion confinement in the central cell.…”
Section: Ii4 Major Results From Tmxmentioning
confidence: 94%
“…8 In these devices, external fueling is required not only to maintain the plasma density at elevated values but also to prevent the onset of end cell microinstabilities that degrade the central cell confinement. 17 …”
Section: Particle Transportmentioning
confidence: 99%